Implementasi Aplikasi Sway dalam Pembelajaran Pendidikan Agama Islam pada Siswa Kelas XI SMA N 2 Ungaran dan SMK N 1 Kabupaten Semarang - Maro, Ajeng Virga Sawitri; Nursikin, Mukh (CV. Creative Tugu Pena, 2022)
Learning media should have a positive impact on academic achievement and student motivation, but not all media can support it. There are several media that actually reduce the enthusiasm of students to learn so that if you want to use a medium in learning you have to create a new formula so that students can be interested in learning.This study aims to determine PAI learning planning using sway media in class XI students, Knowing the implementation of Islamic Education learning using sway media, Knowing the evaluation of Islamic Education learning using sway media. This study used a qualitative research design using a naturalistic qualitative approach. The data in this study were obtained through observation, interviews, and documentation. Checking the validity of the data the researchers used were source triangulation and method triangulation.The results of this study indicate that, first, PAI learning planning using sway media runs with systematic stages. Second, the implementation of PAI learning using sway media starts from distributing material links to students through WhatsApp groups and google classroom, reading material and being absent. Third, the learning evaluation was carried out using assignments and practice questions and the results of the evaluation of SMA N 2 Ungaran showed an increase in academic achievement and at SMK N 1 Pringapus it was concluded that there was a decrease in academic achievement. Keywords: Implementation Sway Application, Sway Application Learning, Islamic Education